Adapting to a changing environment confronting the consequences of climate change - McClanahan, T. R.; Cinner, Joshua E., 1972- (New York : Oxford University Press, 2011)
This title provides tools and a theoretical framework for governments and managers to understand and confront the consequences of climate change. Focusing on coral reefs and the societies that depend on them, the authors examine potential problems and solutions.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 19, 2012).
Includes bibliographical references and index.
Keywords: Climatic changes; Global environmental change